ANALISIS EFEKTIVITAS APLIKASI SISTEM INFORMASI ASET POLRI MENGGUNAKAN METODE TECHNOLOGY ACCAPTANCE MODEL PADA BIRO SARPRAS POLDA JAMBI - Mintaria, Mintaria; Devitra, Joni (Jurnal Manajemen Sistem Informasi, 2019)
In the development of information technology in the goverment and the prive sectors keep on developing a system of information based application. But in fact, there are a lot of application of this system information can not be used effectively buy user. As in the implementantion of property’s of the system information on the facilites and infrastructure office Polda Jambi is still less effective to use. It makes the researcher need to research about the effectiveness of application of Polri propertys system of information which is applied in Polda Jambi’s office of facilities and infsdtructure (Biro Sarpras Polda Jambi) based on the reasercher’s research used Technology Accaptance Model (TAM) as a method, it found that there are 100 respondents filled the questionnaire showed that all of them do not really understand, feel doubt and have no willingness in using that application. So, it makes this application can not be applid effectively